Formação profissional em Serviço Social: estágio supervisionado e a realidade do trabalhador estudante - Castro, Ana Flávia Luca de [UNESP] (2015)
The supervised training is the first moment to meet the professional reality, which gives the opportunity to intern to experience the professional challenges in their daily lives and experience the practice, through contact with theory and practice, in coordination. Therefore, this dissertation presents a reflection on the vocational training in Social Work, especially the supervised training, performed by student workers within the university extension projects. Our main goal is to investigate the reality experience about supervised training experienced by working students within the university extension groups in the course of Social Work, Faculty of Humanities and Social Sciences - UNESP/Campus Franca, having as universe the very college and as position of research the extension university, desk research and field research, which has as subjects four interns workers methodology is guided in the qualitative approach, using thus the bibliographic search, four field supervisors of extension projects, the coordinator, the student representative of the internship committee, and the coordinator of the course Social Work